2021
DOI: 10.23887/jere.v5i1.31420
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Function of Joe Biden’s Victory Speech (Systemic Functional Linguistics View)

Abstract: Text analysis was mainly concerned with the ideational function and textual function. Besides, macro aspect has been regarded as the most text structure examined in previous studies.  Regardless of those three aspects, this study focused on the interpersonal function analysis of political speech text, by taking an example of Joe Biden’s victory speech. The purposed theory namely Systemic Functional Linguistics theory (SFL) was then applied to analyze the text. The analysis was conducted by modifying the speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…(3.5) Waste no more time looking for quick fixes and simply get your hands on... Halliday stated that to command others to do something and to invite the audience to do something is using imperative clauses (Darong, 2021). The sentences above are a direct invitation and statement that aging is a matter.…”
Section: Language Power and Social Practicementioning
confidence: 99%
“…(3.5) Waste no more time looking for quick fixes and simply get your hands on... Halliday stated that to command others to do something and to invite the audience to do something is using imperative clauses (Darong, 2021). The sentences above are a direct invitation and statement that aging is a matter.…”
Section: Language Power and Social Practicementioning
confidence: 99%
“…Similarly, Hillary Clinton and Donald Trump also employ the medium level of modal operators in order to make their speeches less aggressive (Ping & Lingling, 2017). In addition, an observation of Joe Biden victory's speech finds that he uses modalities and pronoun "we" to indicate his close relationship with his people (Darong, 2021).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Not only have a certain structure, organization, and point of view, tour commentaries also bear a certain value and message. Besides, tour commentaries function as an important social medium as they give a significant sign to determine speakers' behavior and information conveyed (Darong, 2021;Fan & Bao, 2019;Feng & Liu, 2010;Määttä et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Employing this theory, previous studies found the meta functions of language used in speech text are determined by process types and context (Bartley, 2018;Darong, 2015;Darong, 2021aDarong, , 2021bKelly, 2020;Kusuma et al, 2018), Furthermore, the studies highlighted that benefits of the the theory in revealing the language function of a text. However, it is important to note that the Systemic Functional Linguistics (SFL) theory is often labelled as a discourse semantics.…”
Section: Introductionmentioning
confidence: 95%